1972
DOI: 10.1002/bjs.1800590822
|View full text |Cite
|
Sign up to set email alerts
|

Central rupture of the liver with massive liver-cell necrosis. A case report and review of the literature

Abstract: A case of massive central rupture of the liver in which the patient became jaundiced is described. Autopsy revealed, in addition to the intrahepatic haematoma, large areas of infarction in the liver, some of which had become infected and had given rise to septic embolization to various organs. There was deranged liver function which is ascribed to the structural changes found in the liver. The occurrence of hepatocellular jaundice with this type of liver injury has not, to our knowledge, been previously record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“… 2 Soni and Persaud reported a 69‐year‐old woman involved in a car crash who sustained a large intrahepatic haematoma, diagnosed but not resected at laparotomy, with development of sepsis, jaundice and renal failure, who died and who demonstrated large areas of hepatic necrosis at autopsy. 3 Hepatic necrosis and abscess at the site of traumatic liver rupture contributed to the death of a multitrauma patient reported by Castleman et al 4 Jona and Goldstein reported a 4‐year‐old girl who sustained a crush injury that resulted in necrosis of the left lobe of her liver, and, after developing septic shock, was treated by resection, but unfortunately died postoperatively. 5 Smadja et al reported seven cases of hepatic trauma with sepsis that were referred to their institution from other hospitals, six having had previous operations, all seven treated by delayed hepatic resection with hepatic necrosis confirmed in all, four of seven patients surviving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 Soni and Persaud reported a 69‐year‐old woman involved in a car crash who sustained a large intrahepatic haematoma, diagnosed but not resected at laparotomy, with development of sepsis, jaundice and renal failure, who died and who demonstrated large areas of hepatic necrosis at autopsy. 3 Hepatic necrosis and abscess at the site of traumatic liver rupture contributed to the death of a multitrauma patient reported by Castleman et al 4 Jona and Goldstein reported a 4‐year‐old girl who sustained a crush injury that resulted in necrosis of the left lobe of her liver, and, after developing septic shock, was treated by resection, but unfortunately died postoperatively. 5 Smadja et al reported seven cases of hepatic trauma with sepsis that were referred to their institution from other hospitals, six having had previous operations, all seven treated by delayed hepatic resection with hepatic necrosis confirmed in all, four of seven patients surviving.…”
Section: Discussionmentioning
confidence: 99%
“…Most previously reported cases have been diagnosed either intraoperatively or at autopsy. 1–7 Because 50–80% of liver trauma patients are now treated non‐operatively, 8,9 a greater reliance is placed on imaging modalities to determine the nature and extent of the injury. We describe a case of traumatic liver necrosis documented by magnetic resonance imaging (MRI) and confirmed at operation.…”
Section: Introductionmentioning
confidence: 99%